PENGEMBANGAN DESAIN SEPEDA KAYUH REKREASI TIGA PENUMPANG - Lukmana, Muhammad Arifudin (Bina Teknika, 2016)
Cycles are not only used as transportation, but also sport and recreational utility. Cycle is a cheap and eco-friendly transportation. But it has several disadvantages in comfort and travel distance. Because of its limitation, people these days use cycle for sport and recreational tool. In eco-friendly environments, people are forced to use pollution-free vehicle. Several campuses, parks, factories and offices use cycle to support eco-friendly campaign. Tandem bike is cycle for leisure and driven by two or more person. Family activity, communication, light sport and transportation can be done by driving a tandem bike. This cycling activity is suitable for people who live in the busy city. This paper is studying process of designing a recreational tandem bike for three people. The study compares existing three or four-driver tandem bike with two new concepts. After selection using scoring based on criteria, selected concept is designed in detail. Evaluationsof design use 2 dimension Cremona method and finite element method.